Effect of Combining Inspiratory Muscle Training with Deep Diaphragmatic Breathing Exercises on Diaphragm Excursion in Subjects with Multiple Sclerosis. - Ahmad, Ahmad Mahdi; Ali Ahmed, Reham Ali Mohamed; Hassan, Mai Helmy; Ali, Heba Mohammed (NeuroRehabilitation, 2025)
Objective: Multiple sclerosis (MS) involves respiratory muscle weakness that can lead to critical complications. Inspiratory muscle training (IMT) is a therapeutic intervention that effectively strengthens the respiratory muscles. This study aimed to investigate the effectiveness of IMT combined with deep diaphragmatic breathing exercises with respect to diaphragm excursion, respiratory muscle strength, and fatigue in subjects with MS. Methods: Thirty-six subjects with MS, aged 25–45 years, with mild to moderate disability, were assigned equally to a study and an active control group. The study group (i.e., the IMT group) received IMT combined with deep diaphragm breathing exercises, while the control group received only deep diaphragm breathing exercises. The interventions were provided for 15 min, three days per week, and 8 weeks. The primary outcome measure was diaphragm excursion, and the secondary outcome measures were maximal inspiratory pressure (Pimax), fatigue severity scale (FSS), and pulmonary dysfunction index (PDI). Results: The IMT group showed significantly more improvements in diaphragm excursion (p < 0.001), Pimax (p = 0.002), FSS (p < 0.001), and PDI (p < 0.001) than the control group. Conclusion: IMT combined with deep diaphragmatic breathing exercises could lead to better improvements in diaphragm excursion, inspiratory muscle strength, fatigue symptoms, and PDI than deep diaphragmatic breathing exercises alone in subjects with MS and mild to moderate disability.